Serratiopeptidase: a well-known metalloprotease with a new non-proteolytic activity against S. aureus biofilm. Issue 1 (December 2015) - Selan, L.; Papa, R.; Tilotta, M.; Vrenna, G.; Carpentieri, A.; Amoresano, A.; Pucci, P.; Artini, M.
Abstract Background The use of indwelling medical devices is associated with a significant risk of infections byStaphylococcus aureus (S. aureus ) which possesses a variety of virulence factors including many toxins and the ability to invade eukaryotic cells or to form biofilm on biotic and abiotic surfaces. The virulence factors above described are often related to proteins exposed on the bacterial surface. BlockingS. aureus colonization may reduce the incidence of invasive infectious diseases. Previously reports evaluated the anti-infective properties of serratiopeptidase (Spep), an extracellular metalloprotease produced bySerratia marcescens ATCC 21074 (E-15), in impairing virulence-related staphylococcal properties, such as attachment to inert surfaces and adhesion/invasion on eukaryotic cells. However, to date its mechanism of action is unknown. Methods Spep gene was PCR amplified and cloned into expression vector pET28b(+). The mutant EspepA was constructed from plasmid pET28b-Spep applying the one-step overlap extension PCR strategy. There sulting plasmids were costransformed in EcBL21(DE3) cells with the plasmid pRuW4inh1 harboring the Erwinia chrysanthemi secretion system. Bacterial pellets and supernatants were collected and analyzed by SDS-PAGE and zymography. The unambiguous identification and a detailed structure characterization of both the wild type and the mutant Spep were obtained by mass spectrometric analyses. The resultant supernatants sterilized by filtration were separately used to condition biofilm formation of S. aureus. Quantification was based on crystal violet method. Results In this work we constructed Spep mutant by substituting the glutamic acid in the catalytic site with a residue of alanine. In this manner we were able to evaluate the anti-biofilm activity of Spep mutant in absence of proteolytic activity. As expected, this mutant did not display protease activity but it retained its anti-biofilm properties, suggesting that this action is independent by enzymatic activity. Conclusions New knowledge obtained from data reported in this paper calls attention to a novel mechanism of action of Spep. This protein could be developed as a potential "antipathogenic agent" capable to impair the ability ofS. aureus to form biofilm on prostheses, catheters and medical devices, exploiting a mechanism different from the proteolytic activity.